Measurement of Activated Protein C Resistance during Menstrual Cycle in Women with and without the Leiden Mutation - Wramsby, M. L.; Bremme, K.; Blombäck, M. (Thrombosis and Haemostasis, 2001)
Variations in the APC ratio during the menstrual cycle were assessed in 25 women without the Leiden mutation, and 10 women who were carrier of the mutation. Blood samples were collected at four occasions during one menstrual cycle. APC ratios were measured with two APTT based plasma methods with and without factor V depleted plasma.None of the methods were able to accurately discriminate between mutated and non mutated women in all samples. Although a normalized method with factor V depleted plasma was favorable.The levels of estradiol and progesterone did not differ between mutated and non mutated women.Our findings suggest that the level of estradiol at estimated time of ovulation is of importance for the response to APC during luteal phase, since the women exhibiting the highest levels of estradiol at time for ovulation had the lowest response to APC.
Keywords: Menstrual cycle; APC ratio